STRATEGI PENGEMBANGAN KEMAMPUAN MEMBACA ANAK USIA 4-5 TAHUN MELALUI PERMAINAN ULAR TANGGA - Nur Hidayah, Ana (incrementapedia, 2020)
Abstract The problem faced in this study is the reading ability of children aged 4-5 years old is still low, it is caused by teachers who tend to use classical learning strategies when introducing letters or words. To develop the reading ability of children aged 4-5 years old must be adjusted to the characteristics of early childhood, namely learning through play. One form of game stimulation that is able to develop children's reading skills is the snake and ladder game, by using the snake and ladder game in learning, it is expected that children's reading ability of 4-5 years old will develop optimally. This research uses the action research method, while the research design used is in the form of a cycle that refers to the Kemmis and Mc Taggrat models with the following steps: 1) planning, 2) action, 3) observation, 4) reflection. In this study only reached the planner stage, namely making RRPM, RPPH and snake ladder games that have been modified by researchers to develop reading skills in children aged 4-5 years old, then the learning device is validated by experts and declared to meet practical aspects so that it is feasible to use to develop language skills of children aged 4-5 years old. The population in this study were children aged 4-5 years old at Dharma Wanita I Rowoharjo Nganjuk Kindergarten in 2019/2020, taking a sample of 18 children consisting of 11 boys and 7 girls